Spies and Porters of the Mind in Andre Du Laurens' Discourse of the Preservation of Sight. - Power, Andrew J (Notes & Queries, 2021)
The article focuses on the typographical error in the English translation of French physician André Du Laurens's "Discourse of the Preservation of Sight" by Marion A. Wells. According to the physician, the eyes contribute in the entry of love into the body of a person. It points out that the word potter in the translation is erroneous in light of the context of the discourse. Du Laurens used the metaphor of spies to describe the deception of the eyes as the porters of the soul and mind.